Numerical modelling of hip fracture patterns in human femur. (May 2019) - Marco, Miguel; Giner, Eugenio; Caeiro-Rey, José Ramón; Miguélez, M Henar; Larraínzar-Garijo, Ricardo
Highlights: Human femur fracture has been simulated, distinguishing between different fracture morphologies. The model demonstrated accurate results in elastic regime and fracture load estimation. A sound qualitative analysis of both specimens has been carried out to understand the fracture process. We have observed that the internal distribution of bone mineral density strongly influences the femur fracture morphology. Thanks to a microCT scan fracture has been analysed and compared with the numerical models. Abstract: Background and Objective: Hip fracture morphology is an important factor determining the ulterior surgical repair and treatment, because of the dependence of the treatment on fracture morphology. Although numerical modelling can be a valuable tool for fracture prediction, the simulation of femur fracture is not simple due to the complexity of bone architecture and the numerical techniques required for simulation of crack propagation. Numerical models assuming homogeneous fracture mechanical properties commonly fail in the prediction of fracture patterns. This paper focuses on the prediction of femur fracture based on the development of a finite element model able to simulate the generation of long crack paths. Methods: The finite element model developed in this work demonstrates the capability of predicting fracture patterns under stance loading configuration, allowing the distinction between the main fracture paths: intracapsular and extracapsular fractures. It is worth noting the prediction of different fracture patterns for the same loading conditions, as observed during experimental tests. Results and conclusions: The internal distribution of bone mineral density and femur geometry strongly influences the femur fracture morphology and fracture load. Experimental fracture paths have been analysed by means of micro-computed tomography allowing the comparison of predicted and experimental crack surfaces, confirming the good accuracy of the numerical model.